Kompetensi Komunikasi Klinis Berbahasa Inggris Mahasiswa Keperawatan Ditinjau dari Foreign Language Anxiety dan Self-Efficacy - Nurasia Natsir; Alamsyah Alamsyah; Suntin Suntin (Indo Publishing, 2026)
English clinical communication is an increasingly critical competency for nurses in the era of healthcare globalisation, yet many nursing students experience psychological barriers when communicating in a foreign language in clinical situations. Foreign language anxiety (FLA) and self-efficacy are regarded as two principal psychological factors affecting communication competence. This study examined FLA and self-efficacy as predictors of English clinical communication competence among nursing students at Institut Ilmu Kesehatan Pelamonia. A quantitative predictive correlational cross-sectional design was used. A total of 75 nursing students were selected through proportional random sampling. Data were collected using an adapted FLCAS, the General Self-Efficacy Scale, and a clinical communication competence scale, then analysed with Pearson correlation and multiple linear regression. FLA was negatively related (r = -0.51) and self-efficacy was positively related (r = 0.57) to clinical communication competence. The regression model was significant (F(2,72) = 24.6; p < 0.001), explaining 41% of the variance (R2 = 0.41); both FLA (b = -0.32) and self-efficacy (b = 0.43) were significant predictors. FLA and self-efficacy are significant predictors of English clinical communication competence. Nursing education should reduce anxiety while building students self-efficacy.